Notary Role In Making The Establishment Of The Deed Of Business Cooperation In The Rembang District - Zaenal Arifin; Risky Amalia; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze: 1) The implementation of the Deed of Establishment of Cooperative manufacture in Rembang. 2) The role of the Notary as the maker of the Deed of Establishment of Cooperative Enterprises. 3) Barriers and solutions in the Deed of Establishment of Cooperative Development in Rembang.The approach method in this research is juridical empirical, data sources used are primary and secondary data obtained through interviews and literature study, performed data analysis by descriptive analytic.Results of the research results can be concluded: 1) Implementation of Creation Deed of Establishment of Cooperative in Rembang which starts with the preparation stage of formation, preparation stage meetings of formation, stage meetings of formation, stage request for approval rights of legal entities cooperatives, and the stage of issuance of the deed pendiiran and 2) As the role of Notary Deed of establishment of cooperative enterprises in Rembang is as maker deed of cooperative efforts. Notaries have the right authority / legal standing in a deed of incorporation of cooperatives. 3). Obstacles and solutions in the Deed of Establishment of Cooperative Development in Rembang of the cooperative is a member of the cooperative awareness level is still low, less managerial capacity, and limited capital resources. Barriers of Notary Public Notary is still much limited knowledge of Notary Deed Official Cooperation (PPAK) and the low interest of the Notary Deed Cooperative (NPAK) in Rembang district were registered for the Legal Entity Administration System Cooperative (SISMINBHKOP). With the state of a society, then the Office of Industry Trade Cooperatives and Small and Medium Enterprises Rembang should seek to build cooperation between the Notary in Rembang with the Agency's own cooperative.Keywords: Deed of Establishment of Cooperative; PPAK; SISMINBHKOP